Modern methods of teaching lexics - Eshankulova , Lola (The Lingua Spectrum, 2024)
Modern technologies have significantly changed the language learning process. With the help of computers, smartphones, and internet platforms, learning languages has become more convenient and effective. This article examines the role of technologies in the development and acquisition of vocabulary. Online dictionaries, mobile apps, and interactive platforms have emerged as essential tools for expanding one's lexicon. Technologies provide opportunities to quickly learn new words and apply them in daily life. The article also discusses the potential negative aspects of technology use in language learning, as they can sometimes alter traditional methods and lead to misinterpretations.